KEBIJAKAN, PRINSIP-PRINSIP AKREDITASI SEKOLAH / MADRASAH, DAN PERAN SATUAN PENDIDIKAN DALAM PROSES AKREDITASI - Muhammad Abdillah; Kurnia Syiffa’ul Husnah; Husnul Yaqin; Hilmi Mizan (PT. Hasba Edukasi Mandiri, 2026)
Accreditation is a crucial external quality assurance instrument to assess eligibility and drive continuous quality improvement in educational institutions. However, the accreditation process is often perceived by educational units merely as an administrative compliance burden rather than a momentum for evaluative reflection to improve actual quality. This paper aims to analyze the governance policy of school and madrasah accreditation in Indonesia, dissect the principles of accreditation implementation, and formulate the strategic roles that educational institutions must undertake to succeed in the accreditation process. The method used in this study is library research with a qualitative-descriptive approach through critical analysis of government regulations, National Accreditation Board (BAN) guidelines, and literature on quality assurance in Islamic education. The results indicate that current accreditation policies have shifted from a compliance-based paradigm to a substantive performance-based paradigm. The implementation of accreditation is strictly governed by the principles of comprehensiveness, objectivity, fairness, transparency, accountability, and professionalism. The practical implication of this study requires educational institutions to take a proactive role through establishing Internal Quality Assurance Teams (TPMI), conducting honest school self-evaluations (EDS), and fulfilling authentic performance evidence so that accreditation results can reflect and accelerate institutional quality sustainably.